(untitled) (Archives of Clinical and Medical Case Reports, 2021)
A 61-year-old woman presented with coral reef aorta (CRA) owing to Takayasu’s arteritis (TA) complicating infective aortic aneurysms. Though antibiotic therapy was continued, infective aortic aneurysms were growing, so urgent surgical treatment was required. First, we performed thoracic endovascular aortic repair (TEVAR) using trans-subclavian access, followed by open repair. TEVAR access and landing zone are limited in CRA cases. Moreover, the risk of persistent infection may be important in the situation where sepsis is ongoing. Few reports describe CRA complicated by infected aortic aneurysms. We describe a method of surgical treatment for this condition.